Pengaruh Manjemen Laba dan Tax Avoidance Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Chindy Annisa Violeta; Vanica Serly (Universitas Negeri Padang, 2020)
The puspose of this study is to determine the effect of earnings management and tax avoidance on firm value. This type of research is quantitative. The study was conducted on banking companies listed on the Indonesia Stock Exchange in 2014-2018, with a total sample of 135 samples using a purposive sampling method. Data collection methods are documentary studies. The analysis was done by using multiple regression model. Earnings management is measured using discretionary accruals that are calculated using the performance matched model and tax avoidance is measured using an effective tax ratio (ETR). The results of this study indicate that (1) earnings management has a positive but not significant effect on firm value. (2) Tax avoidance has a significant negative effect on firm value. Recommendations for futher research are expected to expand the object of research becouse in this study only examines banking companies. In addition, future research can use other models as a measurement of earnings management and look for other independent variables if you want to do the same research.Keywords: Earnings Management; Tax Avoidance; Firm Value.